Effects of Phytoestrogen Supplement on Quality of Life of Postmenopausal Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (1st April 2019) - Peng, Ching-Ching; Liu, Chia-Yu; Kuo, Nai-Rong; Tung, Tao-Hsin
Abstract : Background . The effect of phytoestrogen on postmenopausal quality of life is unclear. This study evaluated the effects of phytoestrogen supplement on quality of life for postmenopausal women. Methods . We conducted a systematic review and meta-analysis of randomized controlled trials on the effects of phytoestrogen supplements on the quality of life of postmenopausal women. We searched PubMed, MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials on March 31, 2018, for relevant randomized controlled trials. Two authors independently selected studies, assessed risk of bias, and extracted data. Disagreement was resolved through discussion with a third author. Results . We involved 10 articles in the systematic review. 8 studies and a total of 1, 129 subjects were included in the meta-analysis. The questionnaires used in the evaluation of quality of life were as follows: SF-36, 4 studies; MENQOL, 4 studies; For Short Form 36 surveys, phytoestrogen groups scored significantly higher for body pain (mean difference = 3.85, 95% confidence interval [CI] = [1.14, 6.57], P < 0.01), mental health (mean difference = 4.01, 95% CI = [1.49, 6.57], P < 0.01), and role limitations caused by emotional problems domains (mean difference = 3.83, 95% CI = [1.81, 5.85], P < 0.01). No statistically significant difference was obtained from Menopause-Specific Quality of Life surveys (vasomotor domain mean difference 0.14, 95% CI = [−0.08, 0.36], P = 0.20; physical domain mean difference 0.20, 95% CI [−0.08, 0.48], P = 0.15; psychological domain mean difference −0.10, 95% CI [−0.26, 0.07], P = 0.27; sexual domain mean difference −0.17, 95% CI [−0.42, 0.09], P = 0.19). Conclusion . Current evidence does not support phytoestrogen supplementation improving postmenopausal quality of life. Further comprehensive trials or long-term follow-up studies are warranted.